CREATING THE RESOURCES OF HUMAN CAPITAL IN POLAND (Research Bulletins of the Faculty of Economic Sciences, 2021)
Thanks to the contribution of American scholars, for already several decades hu-man capital has been regarded as the main factor stimulating economic growth. Its fun-damental element is education and its level in the society. This has become the subject of the present paper. The main purpose of the article is the presentation of the dynamics and present state of the educational level of the population of Poland against the back-ground of the demographic transformation. The survey encompasses the period of 2000-2006 and makes use of (among other sources) national censuses of 1998 and 2000 in-cluding the classification into rural and urban areas (villages and towns).
Keywords: human capital, human resources, educational level